Comparative academic achievement of black and white sixth grade students at Lily Hill School, Clark Air Base, Philippines - Tiler, Glenn W. 1930- (1976)
The objective of the study is to know whether the administer of black and white students at Lily Hill School affect their academic achievement. The Iowa Tests of Basic Skills was administered to the sixth grade students at Lily Hill School. This battery of tests consists of subtests in the area of reading comprehension, language arts, mathematics and the work-study skills. Each of these areas is broken down into various components. The test data showed that there was significant difference between the scores of the groups in each of the four main test areas, and also overall, at the .01 level of confidence. The data also showed small differences in achievement between the males and the females on the tests, with the females coming out on the males on all but the mathematics tests. The differences were insignificant.
Appendices: leaves 95-132
Mimeographed.
Vita.
Thesis (M. Education)--University of the Philippines, Diliman.
Keywords: Intercultural education; Academic achievement; Race problems